Transferred war workers, 1942 (1942)
1942 1939-1945 "Transferred war workers, 1942" [hfr0200], 1942 The dispersal of factories and the building of Royal Ordnance Factories in isolated areas required war workers to be transferred all over the country. There were often problems with poor accommodation or travel arrangements, which led to low morale and many of the workers returning home. In March 1941, the Ministry of Labour launched a new programme to support transferred workers which included offices at key railway stations to welcome and advise workers, more hostels, travelling allowances and rest homes for short holidays. To maintain morale, clubs and recreation centres were opened, ENSA [the Entertainments National Service Association] extended its music and film shows to munitions workers and the BBC broadcast Music While You Work twice a day. This article is from the Ministry of Labour's Production and Engineering Bulletin, November 1942.